Menghidupkan matematika abstrak: eksplorasi kebutuhan siswa sma terhadap worksheet berbasis virtual reality - Nur Hidayah, Hikmah; Handayani, Ratih (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study analyzes the necessity of developing Virtual Reality (VR)-based mathematics worksheets to mitigate cognitive barriers in visualizing abstract concepts, while simultaneously addressing the literature gap concerning the integration of immersive technology into self-directed learning tools. Design/methodology/approach: Employing a descriptive qualitative design, the study involved tenth-grade students and mathematics educators at SMA Negeri 1 Kotabumi. Data were collected through semi-structured interviews and analyzed using the Miles and Huberman model to ensure analytical rigor and validity. Findings: The findings confirm that an over-reliance on conventional lecture-based methods triggers motivational stagnation and conceptual visualization difficulties. The needs analysis underscores the urgency of interactive-contextual media to transform students from passive recipients into exploratory learners. Practical implications: These results offer a strategic framework for educational institutions to integrate VR into the mathematics curriculum, enhancing literacy and numeracy outcomes in alignment with the characteristics of the digital generation. Originality/value: The significance of this research lies in identifying the specific requirements for embedding VR into worksheet structures, providing an innovative solution that synergizes self-regulated learning with immersive simulations.   Purpose: Penelitian ini menganalisis kebutuhan pengembangan worksheet matematika berbasis Virtual Reality (VR) untuk mengatasi hambatan kognitif dalam memvisualisasikan konsep abstrak, sekaligus mengisi celah literatur mengenai integrasi teknologi imersif dalam media pembelajaran mandiri. Design/methodology/approach: Menggunakan desain kualitatif deskriptif, studi ini melibatkan siswa kelas X dan pendidik di SMA Negeri 1 Kotabumi. Data dihimpun melalui wawancara semi-terstruktur dan dianalisis menggunakan model Miles dan Huberman untuk menjamin validitas temuan. Findings: Temuan mengonfirmasi bahwa ketergantungan pada metode ceramah memicu stagnasi motivasi dan kesulitan visualisasi konsep. Analisis kebutuhan menekankan urgensi media interaktif-kontekstual untuk mentransformasi siswa menjadi pembelajar eksploratif. Practical implications: Hasil penelitian memberikan landasan strategis bagi institusi untuk mengadopsi VR dalam kurikulum guna meningkatkan capaian literasi dan numerasi sesuai karakteristik generasi digital. Originality/value: Nilai utama penelitian ini terletak pada identifikasi kebutuhan spesifik integrasi VR ke dalam struktur worksheet, menawarkan solusi inovatif yang menggabungkan kemandirian belajar dengan simulasi imersif.